1999
DOI: 10.1021/bi990305u
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Crystal Structure Determination of Recombinant Human Epidermal-Type Fatty Acid Binding Protein,

Abstract: We describe the crystal structure of human epidermal-type fatty acid binding protein (E-FABP) that was recently found to be highly upregulated in human psoriatic keratinocytes. To characterize E-FABP with respect to ligand-binding properties and tertiary structure, we cloned the respective cDNA, overexpressed the protein in Escherichia coli and purified it to homogeneity by a combination of ion-exchange and size-exclusion chromatographic steps with a yield of 30 mg/L broth. The purified protein revealed a 5-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 41 publications
(57 reference statements)
6
98
1
5
Order By: Relevance
“…Linoleic Acid Binds FABP5 in Two Distinct ConformationsThe FABP5-LA interactions are in general very similar to those previously described by Hohoff et al (54) in their analysis of FABP5 complexed to an E. coli fatty acid. The carboxylic headgroup of LA forms a salt bridge with Arg-129, as well as a hydrogen bond with the hydroxyl moiety of Tyr-131.…”
Section: Overall Structure and Oligomerization Status Of Apo-andsupporting
confidence: 82%
See 2 more Smart Citations
“…Linoleic Acid Binds FABP5 in Two Distinct ConformationsThe FABP5-LA interactions are in general very similar to those previously described by Hohoff et al (54) in their analysis of FABP5 complexed to an E. coli fatty acid. The carboxylic headgroup of LA forms a salt bridge with Arg-129, as well as a hydrogen bond with the hydroxyl moiety of Tyr-131.…”
Section: Overall Structure and Oligomerization Status Of Apo-andsupporting
confidence: 82%
“…Because recombinant FABP5 co-purifies with E. coli LCFAs, delipidation/denaturation of the protein followed by refolding was performed prior to LA exposure and subsequent crystallization (42,54). The structure of apo-FABP5 was solved in the P4 3 2 1 2 space group at high resolution (1.67 Å), with the asymmetric unit comprised of a FABP5 monomer adopting the canonical iLBP fold (Fig.…”
Section: Overall Structure and Oligomerization Status Of Apo-andmentioning
confidence: 99%
See 1 more Smart Citation
“…Although two of these cysteines are in isolated positions, the other four are paired in close vicinity. Despite the absence of any reducing agent in the crystallization media, these authors (27) report one oxidized (Cys-120 -Cys-127) and one reduced (Cys-67-Cys-87) cystine. The remarkable feature in the case of FABP is that Cys-67 and Cys-87 are still located close enough to be able to form a covalent bond without any structural rearrangements.…”
Section: Discussionmentioning
confidence: 95%
“…Ligand binding studies have revealed high affinity for oleate and arachidonate but little or no affinity for prostaglandin E 2 (34). Palmitic acid binding to E-FABP has been structurally defined by a combination of x-ray crystallography and high field NMR (35,36). The region of the protein in proximity to the C-5 C-6 methylene groups of the bound fatty acid is structurally restricted and excludes crystallographically ordered water.…”
Section: Discussionmentioning
confidence: 99%